(untitled) (Nexo Revista Científica, 2020)
The objective of this work was to evaluate the physical-chemical and sensorial parameters of the coffee pulp (Coffea arabica), of the Catuaí, Lempira and Parainema varieties, coming from different altitude levels at 1275 masl, 1461 masl and 1550 masl, used as parameters of quality control for the development of infusion-type beverages. Homogeneous samples of 1 kg of pulp of each variety and altitudinal floor were used. The response variables were soluble solids (° Brix), hydrogen potential (pH) and cup profile from descriptive tests with expert judges from the company Organic Coffee Márcala, Anonymous Society (COMSA). The results indicated that the Catuaí variety presented the best response in the variety-altitude interaction, determining values of 15.9 ° Bx, a pH of 5.45, at an altitude level of 1550 masl, also reflecting a better profile in cup with 83% describing a fruit hue. The interaction of these variables plus the control of the fermentation kinetics of the grain determine the final quality of the infusion type drink.